Hybrid nanostructured Ag/ZnO decorated powder cellulose fillers for medical plastics with enhanced surface antibacterial activity - Bazant, Pavel; Kuritka, Ivo; Munster, Lukas; Machovsky, Michal; Kozakova, Zuzana; Saha, Petr (Journal of materials science. Materials in medicine, 2014)
Hybrid inorganic-organic fillers based on nanostructured silver/zinc oxide decorations on micro-cellulose carrier particles were prepared by stepwise microwave assisted hydrothermal synthesis using soluble salts as precursors of silver and zinc oxide. Hexamethylenetetramine was used as precipitating agent for zinc oxide and reducing agent for silver. The inorganics covered all available surfaces of the cellulose particles with a morphology resembling a coral reef. Prepared particulate fillers were compounded to medical grade poly(vinyl chloride) matrix. Scanning electron microscopy and powder X-ray diffractometry were used to investigate the morphology and crystalline phase structure of fillers. The scanning electron microscopy was used for morphological study of composites. With respect to prospective application, the composites were tested on electrical and antibacterial properties. A small effect of water absorption in polymer composites on their dielectric properties was observed but no adverse effect of water exposure on prepared materials was manifested. Electrical conductivity of fillers and composites was measured and no influence of water soaking of composites was found at all. The surface antibacterial activity of prepared composites was evaluated according to the standard ISO 22196. Excellent performance against Escherichia coli and very high against Staphylococcus aureus was achieved.
Keywords: nanokompozity; prášky, zásypy, pudry; oxid zinečnatý; Polyvinyl Chloride; Biocompatible Materials; polyvinylchlorid; Cell Survival; Metal Nanoparticles; Silver; fyziologie bakterií; velikost částic; Zinc Oxide; kovové nanočástice; Nanocomposites; testování materiálů; povrchové vlastnosti; Bacterial Physiological Phenomena; viabilita buněk; Anti-Bacterial Agents; Materials Testing; Cellulose; Surface Properties; Powders; celulosa; biokompatibilní materiály; Particle Size; antibakteriální látky; stříbro